2007
DOI: 10.1007/s00421-006-0382-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial coupling in humans: assessment of the P/O2 ratio at the onset of calf exercise

Abstract: Coupling of oxidation to ATP synthesis (P/O2 ratio) is a critical step in the conversion of carbon substrates to fuel (ATP) for cellular activity. The ability to quantitatively assess mitochondrial coupling in vivo can be a valuable tool for basic research and clinical purposes. At the onset of a square wave moderate exercise, the ratio between absolute amount of phosphocreatine split and O2 deficit (corrected for the amount of O2 released from the body O2 stores and in the absence of lactate production), is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…This uncoupling was found in sedentary young subjects (P/O=1.4) relative to active individuals (2.1) of the same age. Independent approaches have confirmed greater coupling in university students (P/O=2.1; Cettolo et al, 2007) and active adults (P/O=2.4; Conley et al, 2013b) that approach the theoretical maximum (2.3-2.5; Brand, 2005). Isolated mitochondria studies also found improved coupling in athletic individuals (e.g.…”
Section: Uncoupling In Musclementioning
confidence: 93%
“…This uncoupling was found in sedentary young subjects (P/O=1.4) relative to active individuals (2.1) of the same age. Independent approaches have confirmed greater coupling in university students (P/O=2.1; Cettolo et al, 2007) and active adults (P/O=2.4; Conley et al, 2013b) that approach the theoretical maximum (2.3-2.5; Brand, 2005). Isolated mitochondria studies also found improved coupling in athletic individuals (e.g.…”
Section: Uncoupling In Musclementioning
confidence: 93%